A General Equilibrium Model of Production, Interregional Trade, and Location of Industry - Moses, Leon N. (The Review of Economics and Statistics, 1960)
T HIS paper contains a model that emphasizes the intimate connection between interregional trade and the location of economic activity. The author has blended input-output and linear programming techniques in order to achieve substitution and optimization within a general equilibrium framework. What emerges is a multi-region, multi-commodity, empirical study in comparative advantage. To the author's knowledge, it is the first such study. The Census regions of the United States are the areas analyzed. However, the model can be applied to most groupings of regions for which transfer costs rather than artificial restrictions are the major impediments to trade. It also seems likely that a related approach could contribute to understanding the problems of adaptation which confront members of the European Common Market and other contemplated economic unions. As mentioned above, the model synthesizes two approaches to interregional analysis: linear programming as applied to transportation problems, and regional input-output methods. These two techniques have been applied to quite different problems in the past. Three things are taken as given in the typical linear programming transportation study: (i) quantities of a specified good that are available at a number of originating points; ( 2) quantities of the good that are required at a number of destinations; (3) the cost of transporting a unit of the good from each origin to each destination. The problem is to find a network of trade which will satisfy the requirements with a minimum total expenditure on transportation. Thus, the transportation model concentrates on an individual good and sDecifies nothingz so far as interindustry relationships are concerned. It begins with known regional production and consumption and determines the network of trade for a specified good. Regional input-output techniques emphasize the interconnections between industries. Their aim is to determine outputs and requirements of all goods in all regions. To accomplish this, these studies have found it necessary to make assumptions regarding patterns of trade. In one way or another they have treated trade patterns as a datum. It is precisely this aspect of regional input-output analysis that is changed in the present study. Trading patterns as well as regional outputs and requirements of all goods are determined. The model involves the introduction of alternative production techniques and substitution into input-output analysis. This substitution takes place between regions. However, the model can be adapted to permit substitution between industries and between different technological layers of the same industry. The paper is divided into three sections. The first contains a description of the basic model. The second contains a brief explanation of the data and computational difficulties and how these difficulties were overcome by making adjustments in the model. The final section contains some of the empirical results and an analysis of these results. Thus, the first section will help the reader to comprehend more readily the empirical analysis and the reasons behind some of its restrictive assumptions. It also brings to light certain important issues which the empirical analysis must ignore. The second section, on the other hand, will help the reader to understand the process whereby the conceptual scheme was converted into an empirical study.